Canine corpus luteum regression: Apoptosis and caspase-3 activity - Luz, Marcelo Rezende; Cesario, Maria Dalva [UNESP]; Binelli, Mario; Lopes, Maria Denise [UNESP] (Elsevier B.V., 2006)
The present study evaluated the occurrence of apoptosis and caspase-3 activity in the canine corpus luteum during the period of luteal regression in eight pregnant and nine nonpregnant diestrus bitches. Intact luteal cells were obtained from corpora lutea in both peripartum pregnant bitches and nonpregnant diestrus bitches at approximately 65 d (range 63-68) after estrus, but not at days 75 and 85 in nonpregnant bitches. In all bitches, apoptotic cells were rarely detected and when present, those cells were more easily detected using the hematoxylin and eosin technique than using the critical electrolyte concentration technique. The luteal structures at 75 and 85 d of diestrus had histological characteristics similar to a corpus albicans. Caspase-3 activity was detected in morphologically normal corpora lutea from both pregnant and diestrus bitches around day 65, and also in the later structures considered corpus albicans tissue. These results suggested that apoptosis may not be the major mechanism involved in canine functional luteal regression, and that caspase-3 participated in both functional and morphological luteolysis and in the tissue reorganization involved in corpus albicans formation. (c) 2006 Published by Elsevier B.V.
Keywords: bitch; corpus luteum; apoptosis; caspase-3; luteal regression